Senegal : Staff Report for the 2001 Article IV Consultation, First Review Under the Third Annual Arrangement Under the Poverty Reduction and Growth Facility, and Request for Waiver of Performance Criteria. (IMF Staff Country Reports; Country Report ;, 2001)
Faced with a tight liquidity situation at the treasury, the government of Senegal has implemented a tight spending regime to avoid a substantial drawing on the statutory advances at the Central Bank of West African States (BCEAO). Weaknesses in accounting for public funds, as well as the delays in structural reforms, have had fiscal repercussions. Credit growth has reflected the financing needs of the agricultural sector and the buildup of arrears in the energy sector. Recent developments have exacerbated the risk concentration problem in the loan portfolio of the local banking system.